1997
DOI: 10.1126/science.276.5316.1245
|View full text |Cite
|
Sign up to set email alerts
|

Silicon and Oxygen Self-Diffusivities in Silicate Liquids Measured to 15 Gigapascals and 2800 Kelvin

Abstract: Mass transport properties of silicate liquids exhibit complex behavior as a function of pressure, as the tetrahedral framework structure of the liquid shifts to a more compact arrangement of atoms. For highly polymerized aluminosilicate liquids, oxygen diffusivities pass through a maximum at pressures below 10 gigapascals, whereas up to 15 gigapascals diffusivities continue to increase for sodium tetrasilicate liquid. A diffusivity maximum indicates a change in the mechanism of formation of 5-coordinated silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
125
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(142 citation statements)
references
References 33 publications
16
125
1
Order By: Relevance
“…4A). Oxygen diffusivity and bulk viscosity are expected to be anticorrelated for the CNAS melts studied here assuming the Stokes-Einstein relationship, which is consistent with the experimental trend for partially depolymerized melts (8). Based on the Adam-Gibbs theory, the configurational entropy (S config ) of CNAS melts is expected to show a similar pressure dependence with diffusivity (42).…”
Section: O-17supporting
confidence: 65%
See 2 more Smart Citations
“…4A). Oxygen diffusivity and bulk viscosity are expected to be anticorrelated for the CNAS melts studied here assuming the Stokes-Einstein relationship, which is consistent with the experimental trend for partially depolymerized melts (8). Based on the Adam-Gibbs theory, the configurational entropy (S config ) of CNAS melts is expected to show a similar pressure dependence with diffusivity (42).…”
Section: O-17supporting
confidence: 65%
“…For instance, the solubility of Ar into melts increases with increasing pressure and then decreases drastically with a further increase in pressure, with data suggesting a strong composition dependence (7,10,11). Similarly, complex behaviors were reported for the diffusivity and viscosity of silicate melts at high pressure (8). Although the trend in the silica activity in the melts at high pressure is not known, phase relations of mantle melts and minerals imply varying activity coefficients of the oxide in silicate melts with changes in pressure (12)(13)(14).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, interesting macroscopic properties of silicate melts, such as viscosity or diffusion, show significant changes with pressure. 1,2 Many experimental studies on silicate glasses, the base material for various multi-components silicate systems, have suggested that those macroscopic properties were related to atomic-scale structural changes 3 such as angles 4,5 or coordination number [5][6][7] . Densified sodium silicate is a very interesting system to be investigated as it shows the effect of polymerization and depolymerization 5,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies report D(O) maxima in polymerized silicate melts along isothermal compression, for example, B5 GPa for albite 23 and dacite 24 , and B8 GPa for Na 3 AlSi 7 O 17 (ref. 23), implying a reversal in pressure dependence. MD simulations on SiO 2 melt (NBO/T ¼ 0) also reveal maxima in O and Si self-diffusivity on compression 5,25 .…”
mentioning
confidence: 99%